Antiproliferative effect of GTS‑21 in glioblastoma cells - Kolodziej, Malgorzata; Gött, Hanna; Kopischke, Benjamin; Bender, Michael K. F.; Weigand, Markus A.; Di Fazio, Pietro; Schwarm, Frank P.; Uhle, Florian (Oncology letters, 2021)
Glioblastoma multiforme (GBM) is the most common malignant brain tumour in adults. The poor prognosis and short median overall survival of patients with GBM is associated with resistance to therapy after surgical and adjuvant treatment. The expression of various acetylcholine receptors (AChR) in GBM has been widely reported. The present study aimed to investigate the expression of cholinergic system‑related genes in primary GBM and to explore the antiproliferative effect of 3‑(2,4‑dimethoxybenzylidene) anabaseine (GTS‑21) in GBM cell lines. Therefore, the expression of 28 genes associated with the cholinergic system was detected using a customized RT2 Profiler PCR Array in 44 GBM and 5 healthy control brain tissue samples. In addition, the activity of GTS‑21, an alpha 7 subunit nicotinic AChR (α7 nAChR) agonist, and that of α‑bungarotoxin (α‑BTX), an α7 nAChR antagonist, was determined in primary and established GBM cells. Therefore, the A172, U87 and G28 cell lines and primary GBM cells were treated with GTS‑21, ACh or nicotine. Cell viability was evaluated using MTT assay at 24, 48 and 72 h following cell treatment with the corresponding compounds. The results revealed that the expression of cholinergic system‑related components was notably downregulated, except that of cholinergic receptor nicotinic alpha 7 subunit (CHRNA7), in primary GBM and U87 cells. However, the dominant‑negative duplicate form of CHRNA7 was also downregulated. Furthermore, A172 and G28 cells exhibited a heterogeneous gene expression pattern. Additionally, GTS‑21 inhibited the proliferation of GBM cells in a dose‑ and time‑dependent manner. Interestingly, treatment with α‑BTX restored the proliferation of U87 cells, but not that of A172 and G28 cells. Collectively, the findings of the present study suggested that GTS‑21 may inhibit the proliferation of GBM cells and may therefore serve as a novel therapeutic approach to the treatment of GBM, which warrants further investigation.
Gesehen am 19.10.2021